A Comparison of Methylprednisolone and Dexamethasone in Intensive Care Patients With COVID-19. (June 2021) - Ko, Justine J.; Wu, Clay; Mehta, Neha; Wald-Dickler, Noah; Yang, Wei; Qiao, Renli
Objectives: This study retrospectively compares the effectiveness of methylprednisolone to dexamethasone in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or COVID-19) requiring intensive care. Design: This is an institutional review board approved cohort study in patients with COVID-19 requiring intensive care unit (ICU) admission. Patients admitted and requiring oxygen supplementation were treated with no steroids, methylprednisolone, or dexamethasone. Setting: This study takes place in the ICU's at a large, tertiary, public teaching hospital serving a primarily low-income community in urban Los Angeles. Patients: All eligible patients admitted to the ICU for COVID-19 respiratory failure from March 1 to July 31, 2020 were included in this study. Interventions: A total of 262 patients were grouped as receiving usual care (n = 75), methylprednisolone dosed at least at 1mg/kg/day for ≥ 3 days (n = 104), or dexamethasone dosed at least at 6 mg for ≥7 days (n = 83). Measurements and Main Results: All-cause mortality within 50 days of initial corticosteroid treatment as compared to usual care was calculated. The mortality effect was then stratified based on levels of respiratory support received by the patient. In this cohort of 262 patients with severe COVID-19, all-cause mortalities in the usual care, methylprednisolone, and dexamethasone groups were 41.3%, 16.4% and 26.5% at 50 days ( P < 0.01) respectively. In patients requiring mechanical ventilation, mortality was 42% lower in the methylprednisolone group than in the dexamethasone group (hazard ratio 0.48, 95% CI: 0.235-0.956, P = 0.0385). Conclusions: In COVID-19 patients requiring mechanical ventilation, sufficiently dosed methylprednisolone can lead to a further decreased mortality as compared to dexamethasone.